If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 4 = 25 + -3x Reorder the terms: 4 + 4x = 25 + -3x Solving 4 + 4x = 25 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + 4x + 3x = 25 + -3x + 3x Combine like terms: 4x + 3x = 7x 4 + 7x = 25 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + 7x = 25 + 0 4 + 7x = 25 Add '-4' to each side of the equation. 4 + -4 + 7x = 25 + -4 Combine like terms: 4 + -4 = 0 0 + 7x = 25 + -4 7x = 25 + -4 Combine like terms: 25 + -4 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| -5m=80 | | 3x+2=27-2x | | 9x+1=4x+9 | | 0.25ax=3ab | | lm(x+2)-ln(x+1)=1 | | 5x+7y=-2 | | 6x-29=35-10x | | x^3-8x^2+9x=72 | | 1+2x-5x^2=0 | | 3+9x=30 | | 4b^2-9b-46=9 | | 4v^2-10v-17=7 | | 5x-7-4x=6 | | 2n+17=-38-37n | | N^2-2n-18=-3 | | 16.94=3g+3.68 | | N^2-8n+23=8 | | P=2x-2y | | 1.32g-4=0.62 | | y=175+.1*225 | | 5y-5=2y-7+5 | | 6p+1=3(2p+3) | | 3(2g-15)+8g=11 | | X^2-8x+23=8 | | 4x-3x=2x+11 | | 4(x+6)+2=20+4x-6 | | 4m+m=15 | | -24+15-22z=31 | | 5x+6y=22 | | w+(w*2-5)=146 | | 3n-24=14-30 | | -81-9=8x+21 |